Efeitos do envolvimento do aprendiz na aquisição de habilidades motoras com conhecimento de resultados autocontrolado - Lucas Savassi Figueiredo (2014)
Providing the learner control over some of the practice aspects has been demonstrated as beneficial towards motor skill acquisition. Amongst the possibilities of self-control is the schedule of KR, which has shown in several studies advantages over its respective externally controlled Yoked groups. Due to these positive results, recently much attention has turned to better understanding such benefits, through proposing and testing of explanatory hypothesis. Thus, in this study we sought to pair the learner higher involvement induced by the self-control in a Yoked group, which was notified in advance about the KR trials (GA), besides the traditional self-controlled group (GAUT) and Yoked group (GY). The task consisted of transporting one tennis ball in a specified sequence and within a time constraint, in three phases: acquisition, retention and transfer. Thirty undergraduate volunteers of both sexes, aged 18 to 35, all novice in the task, participated of this study. The conducted analysis showed that GA and GAUT were superior to GY in transfer test. The participants also filled out questionnaires which confirmed the preference for receiving KR after what they thought were good trials. The analysis of such trials failed to find the reported data in the questionnaire, once there was no difference in the comparison of trials with and without KR. Considering that GA has shown to be as competent as GAUT, and was not able to individualize KR according to its needs, it is corroborated, therefore, the effects of task involvement and deeper information processing in the self-control of KR in motor skill acquisition.